Pemanfaatan Lingkungan Sekitar sebagai Sumber Belajar Bahasa bagi Anak Usia Dini melalui Media Alam - Sakiah Sakiah; Syamsiah Depalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Early childhood children have a very high curiosity about the world around them. The most effective learning process for them is through direct experience and interaction with the environment. Unfortunately, language learning activities in kindergartens (TK) are often limited to indoor activities, such as reading books or playing word cards. In fact, nature and the environment around the school offer unlimited resources to stimulate children's language development holistically. This research provides an innovative approach to language learning, namely by utilizing natural media in the school environment5. The main goal is to test the effectiveness of nature exploration activities in enriching vocabulary, improving descriptive skills, and encouraging verbal expression in early childhood.